PENGARUH INTEGRITAS DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN DI PT KAMAL UNGGUL ABADI (WINGS) JAKARTA BARAT - Rendy; Liawati (Journal of Research and Publication Innovation, 2025)
This research aims to determine the effect of integrity and communication on employee performance at PT. Kamal Unggul Abadi (wings) West Jakarta. This type of research uses quantitative methods. The sampling technique used saturated sampling and obtained 70 respondents. Data analysis uses validity testing, reliability testing, class assumption testing, regression analysis, correlation coefficient, coefficient of determination and hypothesis testing. The results of this research are that integrity has a significant effect on employee performance by 50.7% and the hypothesis test is obtained tcount>ttable or ( 8,369 > 1,667). Communication has a significant effect on employee performance with a coefficient of determination value of 68.6% and the hypothesis test obtained tcount>ttable or (12,200> 1,667). Integrity and communication simultaneously have a significant effect on employee performance with the regression equation Y = 11.321 + 0.136 X1 + 0.607 X2. The coefficient of determination value is 69.4% while the remaining 30.6% is influenced by other factors. Hypothesis testing obtained a value of fcount>ftable or (75.918>3.134).